Contribution of Madrasah Financing Management in Improving Teacher Performance in Islamic Education Institutions - Hidayat, Ara; Nailan, Akhmaliah Siti; Sariah, Dedeh (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2025)
This study aims to analyze the contribution of madrasah financing management to improving teacher performance at MTs Persis 40 Sarongge. The background of this study is the importance of financing management as a supporting element in improving the quality of education through optimal teacher performance. This study used a quantitative method with a correlation design. The population consisted of 21 teachers, and data collection was done through questionnaires with descriptive and inferential analysis. The results showed that the average madrasah financing management was in the very good category (80.81), while the average teacher performance reached a score of 76.95. Spearman Rank correlation analysis revealed a very strong relationship between financing management and teacher performance with a correlation coefficient of 0.858. The contribution of financing management to teacher performance reached 74%, with the rest influenced by other factors. The conclusion of this study confirms that effective planning, organizing, and controlling in madrasah financing management can improve the quality of learning through optimal teacher performance. This study recommends transparent and needs-based financial management strategies to support teachers' professional development.